The Impact of Apron Optimization in Supporting Aviation Services - Dika Anggara, Adha; Rochmawati, Laila; Muti Sazali, Abdul; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Radin Inten II International Airport is an airport located on Jalan Alamsyah Ratu Perwiranegara in Branti Raya Village, Natar District, South Lampung Regency located in the northwest of Bandar Lampung City. When conducting On Job Training research at Radin Inten II International Airport, there was a lack of standard markings and surfaces on the apron. This is because a lot of marking paint has faded and the surface of the apron is uneven. The research methodology used is a quantitative research methodology, namely by describing the circumstances that are happening to the research object. Data were obtained from direct observation, literature studies, and conducting questionnaires. The results of this study show that the apron at Radin Inten II International Airport Lampung still has to be improved in order to meet the standards it should. This can be indicated by the large number of markings that have faded paint and the surface of the apron that is still uneven.